Optimal automatic generation controllers in a multi‐area interconnected power system with utility‐scale PV plants. Issue 4 (13th September 2019) - Wei, Yawei; Jayawardene, Iroshani; Kumar Venayagamoorthy, Ganesh
Abstract : The centralised utility‐scale photovoltaic (PV) plants installation has greatly enlarged their percentage in the bulk power systems, along with the nature uncertainty for the balance of system power and loads. Consequently, the successful integration of solar PV power in large‐scale power systems requires a reliable and efficient multi‐area automatic generation control (AGC) system within the control centre. Specifically, area‐AGCs that perform tie‐line bias control, in which the area frequency regulates the tie‐line power flow, must balance the operational control area supply power‐and‐demand loads within a pre‐tuned parameter set. Traditional AGC control systems have area linear controllers that must be periodically tuned to manage the high fluctuation of PV power. A practical two‐step tuning method to determine the optimal parameters of existing multi‐area AGCs is presented. The proposed method is demonstrated on a five‐area multi‐machine power system with two large PV plants. The power system was equipped with the synchrophasor‐based monitoring system, with a real‐time simulation platform serving as the application host. Results indicated that the two‐step tuning method provides optimal parameters for all the system AGCs over a wide range of PV penetration levels. Typical results demonstrated the effectiveness of the tuned multi‐area AGCs under dynamic conditions and disturbances.